The Concept Of Lean In Acceleration Of Inpatient Patient Return At Royal Prima General Hospital Medan - Landi Kurnia Daeli; Ermi Girsang; Ahmad Raif; Chrismis Novalinda Ginting (INFOKUM, 2022)
Improving the quality of hospital services is still lacking, one of which is the long process of returning inpatients. This happens because there are activities that do not have added value or waste. The lean method is a method that can reduce the waste that occurs and can increase value to consumers. In this study it was conducted at the inpatient installation of RSU Royal Prima Medan. This study uses value stream mapping to map out the return process flow. Next determine the value stream and identify waste.